Attitude and Academic Engagement of Social Sciences Students of Universidad de Zamboanga - Yusop, Rahima; Ajihil, Bashiruddin (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study investigated the relationship between students’ attitudes toward Social Science and their academic engagement. It focused on the cognitive, affective, and behavioral dimensions of attitude, alongside the cognitive, behavioral, emotional, and social aspects of engagement. The primary aim was to assess students’ levels of attitude and engagement and determine the correlation between the two. It also considered whether there is a significant difference between attitude and engagement with respect to demographic factors such as age, sex, and department. Research Design A descriptive-correlational method of investigation was used and both descriptive statistics (frequency, percentage, mean) and inferential statistical analysis (Pearson correlation, t-tests, ANOVA) were applied. Simple random sampling was used to select 350 students in the study. It was found that the students had a positive attitude for Social Science and their academic engagement was also high for all three domains. Moderate, but statistically significant association was found between students’ attitude and their academic engagement. Also, significant differences in attitude and engagement were noticed when it was stratified by age, gender and area study. Thus, the target intervention of the intervention program would aim at enhancing the students’ engagement by means of teaching with active learning strategies and institutional support. Based on the results the study concludes that focused promotion of positive aspects can significantly increase academic engagement and hence result in increased learning within Social Science education.